PENGEMBANGAN PROGRAM MYOB PADA PEMBELAJARAN KOMPUTER AKUNTANSI DI PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS SRIWIJAYA - Deskoni Deskoni; Rusmin AR; Firmansyah Firmansyah (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2018)
This research is aimed to produce MYOB learning materials in accounting computer learning which was valid, practice, and having the potential effects toward the learning achievement. This research prosedure using Rowntree Model which had three stages, which consists of planning, developing, and evaluating. The data validity was done through the expert evaluation stage with the percentage result from the media expert and the material expert show the results of 80% with a valid category used the validation sheet. The data practicality was done through the one-to-one evaluation with the percentage results of 87,5% and small group evaluation with the percentage results of 92,44% in the very practically category through questionnaire. The data potential effects was done through the field test stage using pretest shows the results of 45%. The data posttest shows the results of 85%. It shows an increasing in learning achievement of 40% and it can be concluded that the MYOB learning materials in accounting computer learning which was valid, practice, and having the potential effects toward the learning achievement.